2010
DOI: 10.1002/anie.201001623
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nano/Microstructures at Fluid Interfaces

Abstract: The generation of novel multifunctional materials with hierarchical ordering is a major focus of current materials science and engineering. For such endeavors, fluid interfaces, such as air-liquid and liquid-liquid interfaces, offer ideal platforms where nanoparticles or colloidal particles can accumulate and self-assemble. Different assembly processes and reactions have been performed at fluid interfaces to generate hierarchical structures, including two-dimensional crystalline films, colloidosomes, raspberry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
143
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(147 citation statements)
references
References 182 publications
(192 reference statements)
4
143
0
Order By: Relevance
“…[6][7][8][9][10][11][12] A fundamental role in the underlying physics is played by the capillary deformations of a fluid-fluid interface when it comes into contact with a solid surface. The capillary interactions induced by these deformations can be exploited, for example, in the selfassembly of interface adsorbed colloidal particles, [13][14][15][16] which can be directed by manipulating, e.g., the interface shape, [17][18][19] the particle shape, [20][21][22][23] or the particle concentration. 24,25 The capillary deformations may also play an important role in the adsorption of a single non-spherical colloidal particle at a fluid-fluid interface, which is a recurrent issue in soft matter (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] A fundamental role in the underlying physics is played by the capillary deformations of a fluid-fluid interface when it comes into contact with a solid surface. The capillary interactions induced by these deformations can be exploited, for example, in the selfassembly of interface adsorbed colloidal particles, [13][14][15][16] which can be directed by manipulating, e.g., the interface shape, [17][18][19] the particle shape, [20][21][22][23] or the particle concentration. 24,25 The capillary deformations may also play an important role in the adsorption of a single non-spherical colloidal particle at a fluid-fluid interface, which is a recurrent issue in soft matter (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that if the binding energy of nanoparticles (the energy to detach particles from the interface) is high enough (compared with thermal fluctuations) the adsorption is irreversible. 7,9,40 Equation 1 is used to calculate binding energy of the particles at the interface. In addition to SEM, this is another proof showing irreversible adsorption of the nanoparticles to a PLA melt-air or supercritical CO 2 interface.…”
Section: Figure 4 Interfacial Tension Values Of Pla-silica Aptes Commentioning
confidence: 99%
“…[1][2][3][4][5] In most cases dispersion of the nanoparticles within the polymer matrix of the nanocomposites is desired, however for some applications, such as colloidosomes, nanoparticle-armed polymer latex, Janus structures, and foams and emulsions stabilized by particles, localization is necessary. [6][7][8][9][10] Polymeric foams have the advantages of good mechanical, energy-absorbing, and thermal-insulation properties. 11 One interesting polymer for foam applications is poly (lactic acid) (PLA).…”
Section: Introductionmentioning
confidence: 99%
“…These applications range from self-assembly of membranes [1] and colloidosomes [2], to Pickering emulsion stabilization [3,4]. In contrast to top-down approaches such as lithography and microcontact printing, the self-assembly of particles offers a bottom-up approach to form micro-and nano-structures [2].…”
Section: Introductionmentioning
confidence: 99%